Nanostructured Cr(N,O) based thin films for relative humidity sensing - Ferreira, A. (2021)
This work presents multifunctional coatings prepared by Physical Vapor Deposition with Oblique Angle deposition with relative humidity sensing capability. Thin films based on chromium oxynitride (Cr(N,O)) were prepared with zigzag nanostructures and varying the amount of nitrogen and oxygen in order to enhance the humidity response. The obtained Cr(N,O) thin films show an increasing amount of oxygen as the O2/N2 mixture flow increases, leading to a transition from chromium nitride to chromium oxide. Further, a change from a bcc-Cr to a fcc-CrN phase is obtained as the O2/N2 mixture flow increases, which is attributed to a Cr2N ditrigonal scalenohedral crystalline structure (β-Cr2N) with the presence of a CrO crystalline structure. The amount of oxygen present in the composition of the coating leads to high electrical resistivity, ranging from 1.27 × 10−6 ± 5.02 × 10−8 Ω m for the sample with 16 at. % of O to 4.50 × 109 ± 4.20 × 107 Ω m for the sample with 60 at. % of O. The highest sensibility to the relative humidity (RH) variation from 40% to 80% was 1.87 × 10−2 ± 7.00 × 10−5 (RH %)−1, being suitable for relative humidity sensing applications.